Effect of dynamic high‐pressure microfluidization on the morphology characteristics and physicochemical properties of maize amylose. Issue 5 (12th December 2012) - Tu, Zongcai; Yin, Yuebin; Wang, Hui; Liu, Guangxian; Chen, Lili; Zhang, Peng; Kou, Yu; Zhang, Lan
Abstract Maize amylose–water suspension (6% w/w) was subjected to single‐pass dynamic high‐pressure microfluidization (DHPM) treatment at 80, 120, 160, and 200 MPa, and changes in the morphology characteristics and physicochemical properties were compared with native maize amylose as a control sample. Laser scattering measurements of particle size demonstrated with microfluidization treatment at 80 MPa showed a slight decrease in mean diameter, while a significant increase was observed above 120 MPa. SEM analysis showed that the surface appearances of maize amylose were altered and the starch granules were partially gelatinized after DHPM treatment. The microfluidization treated maize amylose showed elevated light transmittance and swelling power. However, the solubility was decreased and no significant changes in the freeze–thaw stability. DSC analysis showed a decrease in gelatinization temperatures (To, Tc) and gelatinization enthalpy (ΔH) upon high‐pressure treatment. The texture profile analysis of the starch gel prepared from the suspension treated with high pressure obtained higher hardness and adhesiveness, lower cohesiveness and springiness. The results provide the basic information on the physicochemical properties of maize amylose treated at different microfluidized pressures and indicate the potential possibility of DHPM for starch modification.